Current status and trends of green zones use in Kiev - Derkulskyi, R. (Land Management, Cadastre and Land Monitoring, 2017)
The current state of Kyiv city green areas was analyzed in planning, land management,legal and environmental aspects. This article provides comparison per capita greenspace provision between Kyiv and European cities.Keywords: land governance, public land management, acquisition, managementand disposal of state land, green space provision, green areas, city land cadastre,city-plnning cadastre, state land cadaster, urban forests.